Mechanisms of psychological defense and strategies of control stress of mothers who have children suffering from cerebral paralysis - L. M. Kolpakova (Бюллетень сибирской медицины)
The problem of studying adaptive potential of mothers who have children with cerebral paralysis is considered which may be useful for the choice of diagnosis and preventive accesses in the framework of preventive measures directed to the prevention of disturbances of personality and diseases under stress events of life. Analysis data of mechanisms’ structure of psychological defense in the age dynamics compared to control group of women having healthy children. Psychological adaptive mechanisms are differentiated which help to transform negative internal emotions into more adequate form taking into account specificity of the situation in which mothers with such children are. Mechanisms of controlling behavior are revealed which have preventive function and increase personal resources of women-mother in the situation of stress events which are associated with her child disease.